Islam and Pancasila Muhammad Natsir’s Democracy Thought - D. Dardiri (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
The purpose of this paper is to discuss the thougt Muhammad Natsir about Democracy. He was a Muslim intellectual who devoted himself and his life to his people and his country. From our survey of his career, we can see that he was an important figure in the history of the Indonesian revolution. He was an independent as well as critical thinker who was always ready to participate in open debates and polemics in order to discover the truth. He did so not only with his own colleagues, but also with non- Muslims. It was never his intention to attack his opponents, even though he often found himself in the position of defending Islam.